Multimodal Computed Tomography Increases the Detection of Posterior Fossa Strokes Compared to Brain Non-contrast Computed Tomography - Ostman, Cecilia; Garcia-Esperon, Carlos; Lillicrap, Thomas; Tomari, Shinya; Holliday, Elizabeth; Levi, Christopher; Bivard, Andrew; Parsons, Mark W.; Spratt, Neil J. (Frontiers in Neurology, 2020)
Aims: Multimodal computed tomography (mCT) (non-contrast CT, CT angiography, and CT perfusion) is not routinely used to assess posterior fossa strokes. We described the area under the curve (AUC) of brain NCCT, WB-CTP automated core-penumbra maps and comprehensive CTP analysis (automated core-penumbra maps and all perfusion maps) for posterior fossa strokes. Methods: We included consecutive patients with signs and symptoms of posterior fossa stroke who underwent acute mCT and follow up magnetic resonance imaging. Multimodal CT images were reviewed blindly and independently by two stroke neurologists and area under the receiver operating characteristic curve (AUC) was used to compare imaging modalities. Results: From January 2014 to December 2019, 83 patients presented with symptoms suggestive of posterior fossa strokes and had complete imaging suitable for inclusion (49 posterior fossa strokes and 34 stroke mimics). For posterior fossa strokes, comprehensive CTP analysis had an AUC of 0.68 versus 0.62 for automated core-penumbra maps and 0.55 for NCCT. For cerebellar lesions >5mL, the AUC was 0.87, 0.81 and 0.66 respectively. Conclusion: Comprehensive CTP analysis increases the detection of posterior fossa lesions compared to NCCT alone and should be implemented as part of the routine imaging assessment in posterior fossa strokes.